2004
DOI: 10.3201/eid1003.030431
|View full text |Cite
|
Sign up to set email alerts
|

Reemerging Leptospirosis, California

Abstract: Leptospirosis is a reemerging infectious disease in California. Leptospirosis is the most widespread zoonosis throughout the world, though it is infrequently diagnosed in the continental United States. From 1982 to 2001, most reported California cases occurred in previously healthy young adult white men after recreational exposures to contaminated freshwater. We report five recent cases of human leptospirosis acquired in California, including the first documented common-source outbreak of human leptospirosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
89
0
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 17 publications
0
89
0
12
Order By: Relevance
“…La leptospirosis se considera una zoonosis emergente y reemergente de distribución mundial, causada por una bacteria perteneciente al género Leptospira, la cual se adquiere al tener contacto directo o indirecto con orina infectada de animales, suelos, aguas o alimentos contaminados (1)(2)(3)(4).…”
unclassified
“…La leptospirosis se considera una zoonosis emergente y reemergente de distribución mundial, causada por una bacteria perteneciente al género Leptospira, la cual se adquiere al tener contacto directo o indirecto con orina infectada de animales, suelos, aguas o alimentos contaminados (1)(2)(3)(4).…”
unclassified
“…1 Outbreaks of leptospirosis occur after flood or natural disasters but also in association with increasing rat burden in the slums of large cities. [1][2][3][4] Leptospirosis has been traditionally treated with intravenous penicillin in severe cases and oral doxycycline in milder presentations. 5 Guidelines produced by the International Leptospirosis Society and World Health Organization in 2003 recommended high-dose intravenous penicillin for severe disease and oral amoxicillin, ampicillin, doxycycline, or erythromycin for less severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…knowledge of Leptospira serovars affecting animals in Kazakhstan, is necessary for successful specific prophylaxis, and creates an opportunity to develop a complex of measures aimed at discontinuity of epizootic and epidemiological chain. Leptospirosis has been recognized as an important emerging global public health problem because of its epidemic proportions and increasing incidence in both developing and developed countries (21). Based on obtained results, it can be concluded that cattle coming into the market without any clinical signs of the disease could be Leptospira-carriers and thus they represent a risk to human health.…”
Section: Discussionmentioning
confidence: 86%